BOOK REVIEW : Aceh, Indonesia Securing the Insecure State By Elizabeth F. Drexler; Published by University of Pennsylvania: - Wijegoonawardana, Nirmali (My University, 2009)
This book analyses political violence in Aceh to a great extent. The author draws upon her specialized experience as a policy analyst taking into consideration how an understanding about violence is formed and regulated by state politics. She explains this through the lens of corruption. The author argues that each recurrence of politically assessed narratives that does not line up with past experience can weaken the social legitimacy of new institutions. She expands an analysis of corruption in order to guide ethnography for an insecure state. She has archived this by illustrating how bribery and bias are used in the Indonesians’ structure of daily life. She has noted the lack of legitimacy of institutions of law and governance in a double sense by measuring how the historical narratives are used as technologies both for governance and violence.